STRATEGI ADAPTASI TUKANG OJEK DALAM MEMPERTAHANKAN KELANGSUNGAN HIDUP DI KECAMATAN TAMPAN - Tri Yulastin; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study was conducted at Kecamatan Tampan Kota Pekanbaru. The purpose of this research is to know the strategy of motorcycle taxi driver to fulfill family economic need. The focus of this research is the characteristics of motorcycle taxi drivers at Kecamatan Tampan. The technique of determining samples in a purposive sampling and set the number of samples as many as 5 people. The author uses qualitative descriptive method and Instrument data is observation, interview and documentation. Research conducted, the authors found that the strategy of adaptation of motorcycle taxi drivers at Kecamatan Tampan Kota Pekanbaru in meeting the family's economic needs include: Adaptation, Research Subjects in fulfilling their needs as much as possible to familiarize themselves with the current economic limitations. Goal Attainment, Research Subject has a certain motivation in balancing the economic life of the all-well-off. Integration, the subject of research relies on the relationship and solidarity with fellow motorcycle taxi drivers at the motorbike base. Latency, the subject of research in an effort to keep customers looking for a good relationship. Characteristics of motorcycle taxi drivers in Tampan District are as follows: Knowledge of Traffic Rule, Research conducted found that not all research subjects know the traffic rules. Driving Skills, The general subject of research is skilled in operating the vehicle when mocking. Behavior In Traffic, Research Subjects in the crossbar is not uncommon to violate traffic rules caused by the desire of passengers who want to quickly get to the destination.Keywords: Strategy, Adaptation, Ojek